2016
DOI: 10.1093/chemse/bjv088
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Dysfunction in Older Adults is Associated with Feelings of Depression and Loneliness

Abstract: Olfactory dysfunction is a common complaint among physician visits. Olfactory loss affects quality of life and impairs function and activities of daily living. The purpose of our study was to assess the degree of odor identification associated with mental health. Olfactory function was measured using the brief smell identification test. Depressive symptoms were measured by the Center for Epidemiologic Studies Depression scale. Loneliness was assessed by the de Jong-Gierveld Loneliness Scale. Cognition was meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 44 publications
2
36
1
2
Order By: Relevance
“…However, findings are inconsistent regarding the effect of age on the psychological impact of olfactory dysfunction. While some studies found that elderly people with olfactory impairment were more likely to report depression and low quality of life, others found this association to be confounded by low cognitive function or other general health‐related problems . In this study, alterations in smell impairment was a strong predictor for depressive symptoms and major depressive disorder in adults less than 65 years old but not for adults ≥65 years old suggesting the association is likely confounded by the age‐related physical and mental health changes seen in the geriatric population.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…However, findings are inconsistent regarding the effect of age on the psychological impact of olfactory dysfunction. While some studies found that elderly people with olfactory impairment were more likely to report depression and low quality of life, others found this association to be confounded by low cognitive function or other general health‐related problems . In this study, alterations in smell impairment was a strong predictor for depressive symptoms and major depressive disorder in adults less than 65 years old but not for adults ≥65 years old suggesting the association is likely confounded by the age‐related physical and mental health changes seen in the geriatric population.…”
Section: Discussioncontrasting
confidence: 52%
“…While other major sensory impairments such as blindness and hearing loss are known to be associated with mental health disorders, the link between olfactory dysfunction and depression is not as well characterized . Previous studies have associated impairment of olfactory function with worse cognitive function, feelings of vulnerability, increased loneliness, and depressive symptoms . However, these studies had small sample sizes limited to an institution or specific population with oftentimes conflicting results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some decrease in sensitivity to smells is also found in patients suffering from Major Depression, who may endorse cognitive symptoms resembling MCI or even a mild stage of AD, although in their case this condition can be easily reversed by means of anti-depressant therapy. No problems with smell identification and recognition is diagnosed in this patient group [51,52]. For that reason, olfactory tests are considered useful tools, which enable one to successfully distinguish between patients at risk for the disease or suffering from AD from healthy individuals and individuals suffering from Major Depression from those with depression in the course of AD [31,53].…”
Section: Związek Sprawności Węchowej I Sprawności Poznawczejmentioning
confidence: 99%
“…Ponadto stwierdzono, że pacjentów ze zdiagnozowanymi MCI cechowały podwyższone progi węchowe (czyli mniejsza wrażliwość) na rok przed konwersją i diagnozą AD [50]. W przypadku pacjentów chorujących na depresję, którzy mogą zgłaszać objawy poznawcze przypominające MCI lub nawet łagodne stadium AD, stwierdza się również pewne obniżenie wrażliwości na zapachy, które łatwo ulega poprawie po terapii antydepresyjnej (zdolności identyfikacji i rozróżniania zapachów są praktycznie nienaruszone) [51,52]. Z tego względu uważa się, że za pomocą testów sprawności węchowej można z powodzeniem odróżniać pacjentów zagrożonych lub chorujących na AD od osób zdrowych oraz osoby chorujące na depresję od osób z depresją w przebiegu AD [31,53].…”
Section: Specificity Of the Olfactory Impairment In Alzheimer's Diseaseunclassified